Hexacyano Molybdenum Clusters Chalcohalides and Divalent Cations (Zn2+ and Cu2+) for the Design of Extended Polymeric and Supramolecular Frameworks - Daigre, Gilles; Tarasenko, Maria S.; Ledneva, Alexandra Yu.; G. Naumov, Nikolai; Audebrand, Nathalie; Cordier, Stephane (Current Inorganic Chemistry (Discontinued), 2017)
Two new octahedral molybdenum cyanide cluster compounds, namely [Zn(H2O)(en)2Zn(en)2-Mo6Br6Se2(CN)6].2H2O (1) and [Cu(H2O)(en)22Mo6Br6Se2(CN)6].2H2O (2) (en = ethylenediamine), have been synthetized as single crystals. 1 was obtained by slow diffusion of a solution containing [Mo6Br6Se2(CN)6]4- cluster units into a solution of zinc acetate and ethylenediamine. 2 was obtained by slow diffusion of an ammonia solution of [Mo6Br6Se2(CN)6]4- cluster units into a solution of cupper chloride and ethylenediamine. Both compounds were structurally characterized by single-crystal X-ray diffraction analysis. 1 is a bimetallic one dimensional coordination compound and it crystallizes in the orthorhombic system (P212121; Z = 4; a = 10.675(1) Ŭ b = 15.073(2) Ŭ c = 25.812(4) Ŭ V = 4153.3(1) ų at T = 150 K). 2 is a bimetallic H bonded three dimensional compound and it crystallizes in the monoclinic system (P21/c; Z = 2; a = 9.4281(4) Ŭ b = 11.0220(5) Å, c = 21.1494(9) Ŭ β = 100.053(2)°, V = 2164.03(16) ų at T = 296 K).
Keywords: ethylenediamine